Los guandos, caminos que se bifurcan (Dossier: La novela ecuatoriana; lectura compartida y experiencia de complicidad) - Landín Ramírez, Tatiana Cecilia (2022)
This article explores the thematic axes of the novel Los guandos written by Joaquín Gallegos Lara and Nela Martínez in 1935 and 1982, respectively. The review of the corpus of this literary work shows Nela Martínez as a narrator who takes advantage of the initial material of the first author to express her ties with and understanding of the indigenous. Through a poetic language and an evident social-political thought, Nela transforms the proposal of the first author by giving prominence to the subalternized indigenous voices. The author develops another possibility that highlights the indigenous world and its vindictive struggles.